PERAN MEDIA SOSIAL DALAM KOMUNIKASI PUBLIK DI ERA DIGITAL: KAJIAN LITERATUR SISTEMATIS BERBASIS PRISMA - Sari, Mona Nofita; Veri, Jhon (Komunitas Manajemen Kompetitif, 2025)
This study systematically examines the role of social media in public communication within the digital era using the PRISMA approach. Digital transformation has shifted the dominance of traditional media, creating a more interactive and participatory public sphere. The review formulates three key research questions: the effectiveness of social media compared to traditional media, the most effective platforms for public engagement, and changes in consumption patterns and civic participation. From 98 articles collected via Publish or Perish, 35 were selected, and 10 key studies were further analyzed using Covidence. Findings indicate that social media particularly WhatsApp, YouTube, TikTok, and Instagram demonstrates high effectiveness in disseminating information and fostering public engagement. However, this effectiveness is overshadowed by risks such as hoaxes, polarization, and emotionally driven information consumption. The shift from passive to active consumption shows that the public now participates in producing and distributing information in real time. Analysis using VOSviewer identified seven thematic clusters that reveal strong interconnections between social media, democracy, the public sphere, and civil society. The synthesis confirms that social media has replaced traditional forums as the modern public space, while also demanding higher digital literacy and reflective communication strategies to safeguard the quality of democracy and civic participation